Stereo-video landers can rapidly assess marine fish diversity and community assemblages - Matthews, Kinsey E.; Fields, Ryan T.; Cieri, Kathleen P.; Mohay, Jacklyn L.; Gleason, Mary G.; Starr, Richard M. (Frontiers in Marine Science, 2024)
Climate change and anthropogenic stressors affect the distribution, abundance, and diversity of fish communities across the world. To understand rapidly changing biotic communities, resource managers need a method to quickly and efficiently document temporal and spatial changes in community assemblages across various spatial scales. In this study, we describe the use of new video lander tools to survey fish communities in rocky marine habitats on the continental shelf and slope in California, USA. We evaluate how fish diversity metrics determined by video surveys vary among geographically distinct areas. Our results demonstrate that species diversity, evenness, and richness vary spatially across the coast. Furthermore, community assemblages differ at both broad and fine spatial scales because of differences among habitats. Length frequencies and densities of species in this study were similar to those reported in previous studies. As community assemblages and biodiversity metrics shift in response to changing stressors, it is increasingly important to develop tools and methodologies to detect and rapidly monitor these changes.